Detection of carotid occlusive disease by pulsed Doppler spectral analysis. Issue 12 (December 1984) - Russell, D; Lindegaard, K F; Nakstad, P; Nyberg-Hansen, R; Oygarden, K G
Abstract : In this study a new pulsed Doppler spectral analysis system was used for the evaluation of extracranial carotid disease. When compared to the arteriography findings in 224 carotid arteries, the Doppler examination correctly detected all stenoses greater than 25%, all occlusions, all normal vessels, and 43% of stenosis causing a diameter reduction of less than 25%.